PENGARUH STRATEGI DIGITAL TOURISM OLEH KEMENTERIAN PARIWISATADAN EKONOMI KREATIF (KEMENPAREKRAF) TERHADAP PENINGKATAN KUALITAS PELAYANAN PUBLIK DI WATERFRONT CITY PANGURURAN KABUPATEN SAMOSIR - Sitanggang, Sammer Andreas; Siagian, Nalom; Pasaribu, Johnson (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2025)
This study aims to analyze the influence of digital tourism strategies implemented by the Ministry of Tourism and Creative Economy (Kemenparekraf) on improving public service quality in Waterfront City Pangururan, Samosir Regency. The research is based on the strategic role of tourism as a driver of regional economic growth, particularly in Lake Toba, designated as a Super Priority Tourism Destination (SPTD). Although various digital tourism initiatives such as the #DiIndonesiaAja campaign, the Wonderful Indonesia application, and tourist village digitalization have been implemented, their effectiveness still faces challenges such as limited digital platform integration and insufficient digital competence among service personnel. This study employs a quantitative method with an associative approach, involving 99 respondents selected through purposive sampling. Primary data were collected using a Likert-scale questionnaire and analyzed using simple linear regression with SPSS. The results show that digital tourism strategies and public service quality are both categorized as good. Regression analysis confirms that digital tourism strategies have a positive and significant effect on public service quality. These findings highlight that optimizing technology, strengthening promotional content, and enhancing digital capacity of personnel can improve public service quality and strengthen destination competitiveness.